CpG oligodeoxynucleotides are effective in therapy of minimal residual tumour disease after chemotherapy or surgery in a murine model of MHC class I-deficient, HPV16-associated tumours - Reinis, Milan; Símová, Jana; Indrová, Marie; Bieblová, Jana; Bubeník, Jan (International journal of oncology, 2007)
Oligodeoxynucleotides containing guanine-cytidine dimers (CpG ODN) are potent inducers of anti-tumour immune responses. In this study, we analyzed the capacity of CpG ODN to inhibit the growth of both MHC class I-positive and -deficient tumours after debulking the tumour mass by chemotherapy or surgery. We employed an animal model resembling human papillomavirus (HPV) 16-associated tumours. Tumour cell lines with distinct cell surface expression of the MHC class I molecules were injected into syngeneic C57BL/6 mice, and the growing tumours were either subjected to cytoreductive chemotherapy with ifosfamide derivative, CBM-4A, or surgically removed. Subsequent treatment with synthetic CpG ODN significantly blocked the growth of the recurrent tumours. Our results indicate that the therapy with CpG ODN can be effective for the treatment of minimal residual tumour disease of the tumours that have escaped from the immune surveillance by downmodulating the MHC class I expression.
Keywords: Recurrence; Neoplasm, Residual; modely nemocí na zvířatech; Male; Neoplasms; Cell Line, Tumor; CpG ostrůvky; mužské pohlaví; recidiva; Human papillomavirus 16; Time Factors; lidský papilomavirus 16; Animals; lidé; Humans; zvířata; reziduální nádor; časové faktory; myši inbrední C57BL; Disease Models, Animal; myši; Mice, Inbred C57BL; CpG Islands; nádory; Oligonucleotides; nádorové buněčné linie; oligonukleotidy; Mice; geny MHC třídy I; Genes, MHC Class I